Pandas workout - Lerner, Reuven 1970- (Manning Publications, 2024)
Pandas Workout is a thoughtful collection of practice problems, challenges, and mini-projects designed to build your data analysis skills using Python and pandas. The workouts use realistic data from many sources: the New York taxi fleet, Olympic athletes, SAT scores, oil prices, and more. Each can be completed in ten minutes or less. You'll explore pandas' rich functionality for string and date/time handling, complex indexing, and visualization, along with practical tips for every stage of a data analysis project.